2021
DOI: 10.3390/molecules26226899
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Properties of Carvacrol and Magnolol, in Periodontal Disease and Diabetes Mellitus

Abstract: Periodontal disease and diabetes mellitus are two pathologies that are extremely widespread worldwide and share the feature of chronic inflammation. Carvacrol is a phenolic monoterpenoid, produced by a variety of herbs, the most well-known of which is Origanum vulgare. Magnolol is a traditional polyphenolic compound isolated from the stem bark of Magnolia officinalis, mainly used in Chinese medicine. The purpose of this paper is to review the therapeutic properties of these bioactive compounds, in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 174 publications
(306 reference statements)
1
31
0
Order By: Relevance
“…Oregano has also been reported to exhibit potential antibacterial activity and antioxidant properties ( 18 ). Carvacrol, as the predominant bioactive in oregano, has antimicrobial, antioxidant, anti-inflammatory, anti-osteoclastic, and anti-diabetic properties combined with magnolol ( 19 ). Thyme oil has also been reported to exhibit potential antibacterial activity ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oregano has also been reported to exhibit potential antibacterial activity and antioxidant properties ( 18 ). Carvacrol, as the predominant bioactive in oregano, has antimicrobial, antioxidant, anti-inflammatory, anti-osteoclastic, and anti-diabetic properties combined with magnolol ( 19 ). Thyme oil has also been reported to exhibit potential antibacterial activity ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies showed these active substances' minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). Therefore, to prepare the periodontal hydrogel with carvacrol and magnolol, we used the amounts of carvacrol MIC, and MBC indicated in the literature (Figure 2) [21]. To properly formulate these bioadhesive preparations, we have considered several practical aspects for preparation [33].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, more and more plant extracts have been scientifically investigated for their effect on the bacterial flora of periodontal disease. Many of these studies are experimental research on rats, as this animal model has histological, immunological, and biochemical mechanisms similar to those found in humans [19][20][21]. Most medicines have the potential to cause potential side effects, and natural extracts are no exception [22].…”
Section: Introductionmentioning
confidence: 99%
“…To include such underlying mechanisms would allow us to simulate a wider array of drugs, including e.g. antiinflammatory drugs like cd44-inhibitors (31,32), or drugs that influence the size of adipocytes like metformin (33). These potential additions could thus be useful for both drug development and individualized prevention.…”
Section: Limitations With Our Modelmentioning
confidence: 99%